Quantification and Gene Expression Analysis of Histone Deacetylases in Common Bean during Rust Fungal Inoculation - Melmaiee, Kalpalatha (Int J Genomics, 2015)
Histone deacetylases (HDACs) play an important role in plant growth, development, and defense processes and are one of the primary causes of epigenetic modifications in a genome. There was only one study reported on epigenetic modifications of the important legume crop, common bean, and its interaction with the fungal rust pathogen Uromyces appendiculatus prior to this project. We measured the total active HDACs levels in leaf tissues and observed expression patterns for the selected HDAC genes at 0, 12, and 84 hours after inoculation in mock inoculated and inoculated plants. Colorimetric analysis showed that the total amount of HDACs present in the leaf tissue decreased at 12 hours in inoculated plants compared to mock inoculated control plants. Gene expression analyses indicated that the expression pattern of gene PvSRT1 is similar to the trend of total active HDACs in this time course experiment. Gene PvHDA6 showed increased expression in the inoculated plants during the time points measured. This is one of the first attempts to study expression levels of HDACs in economically important legumes in the context of plant pathogen interactions. Findings from our study will be helpful to understand trends of total active HDACs and expression patterns of these genes under study during biotic stress.